The Washington Accord and U.S. licensing boards - Anwar, Arif A.; Richards, D.J. (American Society of Civil Engineers, 2015)
The Washington Accord known as a mutual recognition agreement between national engineering regulatory bodies was signed in 1989 by six founding signatories. Through this mutual recognition agreement the signatories recognize that the formal educational programs accredited by the respective signatories are substantially equivalent. The stated objective of the Washington Accord is to ease the path of engineering graduates to professional registration or licensing in different jurisdictions. Since 1989, the signatories to theWashington Accord has increased threefold with an additional five countries as currently provisional signatories. This rapid expansion is a reflection of the need for international recognition of educational qualifications and competency across borders in an increasingly globalized world. Engineering accreditation bodies, particularly in developing countries, are proactively seeking recognition and mobility of their graduates. Within this context, theWashington Accord celebrates 25 years and charts a course for the next 25 years. This paper examines in detail the position of the U.S. licensing boards on the Washington Accord. It is concluded that with respect to the U.S. licensing boards, the Washington Accord has made only modest inroads in its first 25 years and needs to set a much more ambitious path for the next 25 to achieve truly reciprocal mobility.